Child rearing in the Caribbean : a literature review - Williams, Sian (Caribbean Child Support Initiative [S.l.], 2006)
Seeks to discover the extent of the coverage of the research on childrearing and socialization of young children in the Caribbean and to reflect on the findings. Seeks also to identify cultural process in the socialization of young children (0-8 years) in African Caribbean and Indo Caribbean families residing in the English Speaking Caribbean.